Forest Fire Occurrence Analysis Base on Land Brightness Temperature Using Landsat Data (Study Area: Jalan Kuantan-Pekan, Pahang, Malaysia) - Mohamad Eliyass, Jamaruppin; Bayuaji, Luhur; Ngahzaifa, Ab. Ghani; Rahman, Md. Arafatur; Farid Wajdi, Akashah; Azlan, Shah (Universiti Malaysia Pahang, 2016)

(untitled)
Forest fire has become huge disaster every year, regardless of their causes, be it human activity or nature. While it is difficult to control nature, it is possible to minimizing fire hazards and avoid potential damage by utilizing remote sensing as one prevention step. Remote sensing plays an important role for detecting and mapping forest fires by digitally and minimize cost. This process used Landsat satellite image and integrated with geographic information layer to derive Brightness Temperature. Brightness Temperature were analyzed three observations the data for forest fire for before, during, and after forest fire occur. This study about the forest fire incident occur in year 2014 that located at Jalan Kuantan – Pekan, Kuantan District of Pahang, Malaysia. The result shows the classification of level fire hazard in the study area and also show the transformation of temperature between pre-fire to post-fire.